Application of Cyclodextrins Stabilized Pickering Emulsion in Gluten-free Rice Bread - Xuehong LI; Jingjing GONG; Minjie LI; Dijia XIN; Lu ZHANG; Yong LU (Shipin gongye ke-ji)
To investigate the effect of cyclodextrins (CDs) stabilized Pickering emulsions on the quality of gluten-free rice bread, the corn oil Pickering emulsions stabilized by α-CD, β-CD or γ-CD were prepared and applied to gluten-free rice bread respectively. The specific volume, texture, water distribution and aging enthalpy of the breads were detected. Results showed that the three kinds of CDs-stabilized corn oil Pickering emulsions all had good stability. When they were used in rice bread, it was found that compared with the blank group, both CDs and CDs-stabilized emulsions could increase the specific volume of bread, improve the internal structure and texture characteristics, promote the water holding capacity and delay the aging of rice bread, but the application effects of CDs-stabilized emulsion were more obvious. Among the three types of CDs, α-CD had the best effect on bread quality improvement and anti-aging properties, followed by γ-CD and β-CD. Three CDs-stabilized Pickering emulsions can significantly enhance the quality of rice bread and delay the aging processes.